Psychological variables of CrossFit participants: a systematic review - Serafim T.T.* (2021)
© 2020, Springer-Verlag Italia S.r.l., part of Springer Nature.Objective: This study aimed to review the existing literature concerning the psychological variables of CrossFit participants. Methodology: This review followed the PRISMA guidelines and was documented in the PROSPERO registry (CRD42018091177). Six electronic databases (SCOPUS, PubMed, SPORTDiscus, Web of Science, EMBASE, and Cochrane) were searched from their inception through July 2020. The methodological quality of the studies was assessed. Results: Thirty-four studies met the inclusion criteria. We observed an increase in satisfaction, clinical addiction, and enjoyment among participants related to exercise, social improvement, and high intrinsic motivation to participate for the purpose of enjoyment, challenge, and affiliation. Perceptions of effort were high among CrossFit participants. Some studies found that the reaction time was impaired after the CrossFit session, whereas others found no changes in mental health, self-esteem, and well-being after training. Conclusion: Adherence and maintenance of the practice of CrossFit are related to psychological variables such as motivation and satisfaction of basic psychological needs. CrossFit participants demonstrated high perception of effort, intrinsic motivation, and reasons for practice such as enjoyment, challenge, and affiliation. The quality assessment demonstrated the need for more detail in the methods section of future investigations. Additional high-quality studies are needed to investigate the effects of CrossFit training on the mental health of participants.